From Diagnosis to Survivorship: An Ethnographic Insight into the Lives of Young Adult Cancer Survivors in Indonesia - Nusantara, Prabu (Indonesian Journal of Cancer, 2025)
Background: Cancer remains a significant non-communicable disease in Indonesia, with young adults facing unique challenges due to their developmental stage. Previous research has primarily focused on clinical aspects, neglecting the psychosocial dimensions of cancer survivorship in young adults (aged 20–40 years). Meanwhile, in young adulthood, a person will experience many progressive and integrative changes physically, cognitively and psychologically-emotionally to move towards an increasingly mature and wise personality. The aim of this study is to explore the demographic, sociocultural, and environmental factors influencing the quality of life of young adult cancer survivors in Indonesia, with the objective of identifying their unique challenges and proposing tailored interventions to improve their QoL.Method: This study employs a qualitative ethnographic approach, conducting in-depth interviews and participant observations with 18 young adult cancer survivors aged 20–39 in two cancer shelters in Jakarta. The participants were selected to provide a diverse range of experiences based on gender, marital status, educational background, and length of survivorship. Data were analyzed using MAXQDA 2024, following an inductive approach to identify key themes and insights.Results: The quality of life (QoL) for young adult cancer survivors in Indonesia is shaped by demographic, sociocultural, and environmental factors. Survivors in their twenties faced career disruptions, while those in their thirties struggled with family responsibilities and unmet goals. Gender roles influenced coping, with women often transitioning to homemakers, facing professional limitations, while men dealt with financial stress as providers. Married survivors benefited from spousal support, while single survivors faced challenges in forming new relationships. Higher education levels improved cancer management and health outcomes. Additionally, urban survivors had better access to healthcare and support networks, while rural survivors struggled with misinformation and limited healthcare access, impacting their QoL.Conclusion: The study underscores the necessity for age-specific, gender-sensitive, and culturally tailored interventions to address the unique needs of young adult cancer survivors. Enhanced support systems, education and awareness campaigns, equitable healthcare access, and continuous monitoring and support are recommended to improve their quality of life. Addressing these recommendations can significantly enhance the well-being and recovery of young adult cancer survivors in Indonesia